Multilocus PCR typing strategy for differentiation of Staphylococcus aureus siphoviruses reflecting their modular genome structure - Kahánková, Jana; Pantůček, Roman; Goerke, Christiane; Růžičková, Vladislava; Holochová, Pavla; Doškař, Jiří (Environmental microbiology, 2010)
Given the great biological importance and high diversity of temperate Staphylococcus aureus bacteriophages, a method is needed for the description of their genomic structure. Here we have updated a multiplex PCR strategy for the complex characterization of S. aureus phages of the family Siphoviridae. Based on the comparative genomic analysis of the available phage sequences, a multilocus PCR strategy for typing the major modules of the phage genome was designed. The genomic modules were classified on the basis of the genes for integrase (10 types), anti-repressor (five types), replication proteins polA, dnaC and dnaD (four types), dUTPase (four types), portal protein (eight types), tail appendices (four types) and endolysin (four types) corresponding to the integrase locus, lysogeny control region, and modules for DNA replication, transcription regulation, packaging, tail appendices and lysis respectively. The nine PCR assays designed for the above sequences were shown to be capable to identify the bacteriophage gene pool present both in the phage and bacterial genomes and their extensive mosaic structure. The established multiplex PCR-based multilocus diagnostic scheme is convenient for rapid and reliable phage and prophage classification and for the study of bacteriophage evolution.
Keywords: srovnávací genomová hybridizace; polymerázová řetězová reakce; profágy; DNA, Viral; Genome, Viral; DNA virů; Prophages; Multilocus Sequence Typing; Siphoviridae; Comparative Genomic Hybridization; genom virový; multilokusová sekvenční typizace; Staphylococcus aureus; Polymerase Chain Reaction; virové proteiny; Viral Proteins